Impact of fetal sex on neonatal outcomes in women with gestational diabetes mellitus: a systematic review and meta-analysis - Mahsa Maghalian; Zohreh Alizadeh-Dibazari; Mojgan Mirghafourvand (BMC Pregnancy and Childbirth)
Abstract Background Research on the relationship between fetal sex and neonatal outcomes in pregnant women with gestational diabetes mellitus (GDM) is limited, and existing findings have yielded inconsistent results. Therefore, the aim of our study was to investigate the impact of fetal sex on neonatal outcomes in mothers with GDM. Methods We conducted a systematic search of six database) PubMed, Cochrane Library, Scopus, Web of Science, SID (Persian database), and Embase (up to January 1, 2025. The quality of the included studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. Subgroup analyses differentiated between retrospective and prospective cohorts for the primary outcomes. Sensitivity analyses were performed using the leave-one-out approach to evaluate the robustness of the pooled results. Additionally, a meta-regression analysis was conducted, considering maternal age, gestational weight gain, and BMI for both male and female infants. Results From 702 studies screened, twelve observational studies were included in the analysis. The results revealed a significant increase in the rates of macrosomia (RR 1.47, 95% CI 1.23 to 1.77, 6 studies, 121,230 neonates; p < 0.0001), cesarean delivery (RR 1.05, 95% CI 1.03 to 1.06, 6 studies, 127,704 neonates; p < 0.0001), large for gestational age (LGA) (RR 1.21, 95% CI 1.08 to 1.36, 6 studies, 16,863 neonates; p < 0.0001), small for gestational age (SGA) (RR 1.14, 95% CI 1.05–1.25, 6 studies, 16,863 neonates; p = 0.002), and a 5-minute Apgar score of less than 7 (RR 1.26, 95% CI 1.11 to 1.43, 2 studies, 104,881 neonates; p = 0.0003) in male neonates compared to female neonates. However, there were no significant differences in the rates of preterm delivery (p = 0.86), jaundice (p = 0.75), and a 1-minute Apgar score of less than 7 (p = 0.08) between male and female neonates in women with GDM. Conclusion The findings suggest that male infants are at a greater risk of experiencing specific adverse outcomes in the context of GDM. Further research is needed to establish tailored interventions and guidelines to improve the care and management of women with GDM and their infants.